Villa Arson Nice. (Nice : Villa Arson, 1987)
Boetti, Alighiero ; Armleder, John ; Diao, David ; Federle, Helmut ; Knoebel, Imi ; Mosset, Olivier ; Rockenschaub, Gerwald ; Büttner, Werner ; Kippenberger, Martin ; Oehlen, Markus ; Toroni, Niele ; Parmiggiani, Claudio ; Vermeiren, Didier
Overzicht tentoonstellingen 1986-1987
Frans
boek